Patterns of interpersonal problems and their improvement in depressive and anxious patients treated with psychoanalytic therapy - Salzer, Simone; Leibing, Eric; Jakobsen, Thorsten; Rudolf, Gerd; Brockmann, Josef; Eckert, Jochen; Huber, Dorothea; Klug, Günther; Henrich, Gerhard; Grande, Tilmann; Keller, Wolfram; Kreische, Reinhard; et al. (Bulletin of the Menninger Clinic, 2010)
Interpersonal problems were studied in 121 patients treated with psychoanalytic therapy using the Inventory of Interpersonal Problems. Four characteristic subtypes were identified, which differed in the quality and flexibility of their interpersonal behavior. Independent of the predominant type of interpersonal problems, the psychotherapy treatment led to strong decreases in interpersonal distress and increases in interpersonal differentiation. Psychoanalytic therapy was highly effective for all identified interpersonal subtypes and seems to help patients achieve more satisfactory relationships.